Pengembangan Sumber Daya Manusia dalam Pengentasan Kemiskinan di Kalimantan Timur - Juliansyah Juliansyah; Khoffifah Khoffifah; Khoiriyah Khoiriyah; Daryono Daryono (Syntax Corporation Indonesia, 2024)
This research discusses human resource development (HRD) as a key strategy in poverty alleviation efforts in East Kalimantan. Using a descriptive qualitative approach, this study analyses various factors that influence the quality of human resources and their relationship with the poverty rate in the region. The data used comes from secondary sources, including government reports and statistical data. The results show that improving the quality of education, access to health, and economic empowerment of local communities are key to reducing poverty. This research provides policy recommendations for local and national governments to focus on improving the quality of human capital as a strategic step in poverty alleviation in East Kalimantan.